Cashier Application for Business Washing Service at V2 Laundry and Dry Clean - Rafael Yusia Adi Kusuma; Albertus Dwiyoga Widiantoro; Erdhi Widyarto Nugroho (Soegijapranata Catholic University, 2026)
The laundry business is one of the businesses that continues to grow over time. This business provides laundry services and clothing and other textile care for customers, with the aim of providing convenience, comfort, and quality in maintaining the cleanliness and appearance of their clothes. However, in the era of increasingly rapid digitalization, technological transformation has changed the way various industries operate, including service businesses such as the laundry industry. However, the laundry business still faces challenges in manual operational management, which can hinder efficiency and service quality.This study aims to design and build a web-based cashier application to improve efficiency using the Waterfall method. This application automates order recording, service scheduling, payments, and reporting. Black box testing shows that the application functions according to specifications, while user evaluations show satisfaction with the features and ease of use. With this system, the laundry business can be more efficient, competitive, and integrated with digital innovation.